2020
DOI: 10.1111/jgs.16360
|View full text |Cite
|
Sign up to set email alerts
|

Deintensification of Diabetes Medications among Veterans at the End of Life in VA Nursing Homes

Abstract: OBJECTIVES Many older adults with limited life expectancy and/or advanced dementia (LLE/AD) are potentially overtreated for diabetes and may benefit from deintensification. Our aim was to examine the incidence and predictors of diabetes medication deintensification in older Veterans with LLE/AD who were potentially overtreated at admission to Veterans Affairs (VA) nursing homes (community living centers [CLCs]). DESIGN Retrospective cohort study using linked VA and Medicare clinical/administrative data and Min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 47 publications
3
48
1
Order By: Relevance
“…None of the articles included for full‐text screening, however, were excluded for this reason. A recent study observed that end‐of‐life status may increase the likelihood of deprescribing glucose‐lowering medications in nursing homes 50 . Finally, the quality of many of the included studies was poor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…None of the articles included for full‐text screening, however, were excluded for this reason. A recent study observed that end‐of‐life status may increase the likelihood of deprescribing glucose‐lowering medications in nursing homes 50 . Finally, the quality of many of the included studies was poor.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study observed that end-of-life status may increase the likelihood of deprescribing glucose-lowering medications in nursing homes. 50 Finally, the quality of many of the included studies was poor. When interpreting the results, this was taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…Niznik et al, 2020 10 Umpierrez et al, 2018 11 McCracken et al, 2017 12 Retornaz et al, 2017 13 Walfridsson et al, 2016 14 Dharmarajan et al, 2016 15 Bo et al, 2015 16 To explore predictors for diabetes treatment deintensification…”
Section: Study Details Study Overview Study Design Key Results Commentsmentioning
confidence: 99%
“…In a study published in JAGS of 6960 veterans residing in Veterans Administration Community Living Centers (NHs) with limited life expectance and/or advanced dementia, over 40% were potentially overtreated with hypoglycemic agents (hemoglobin [Hgb] A1C < 7.5%). 15 Less than half of these overtreated patients had deintensification of hypoglycemic treatment over the course of 90 days. In another recent study of 5,471 VA NH residents older than 65 years with type 2 diabetes, 14% met the authorsʼ criteria for overtreatment (Hgb A1C < 6.5% while on insulin).…”
Section: Hypoglycemic Agentsmentioning
confidence: 99%
“…Recurrent episodes of hypoglycemia can result in strokes, worsening cognitive impairment, and many other complications. In a study published in JAGS of 6960 veterans residing in Veterans Administration Community Living Centers (NHs) with limited life expectance and/or advanced dementia, over 40% were potentially overtreated with hypoglycemic agents (hemoglobin [Hgb] A1C < 7.5%) . Less than half of these overtreated patients had deintensification of hypoglycemic treatment over the course of 90 days.…”
Section: Hypoglycemic Agentsmentioning
confidence: 99%